A case of SHORT syndrome with a novel genetic mutation diagnosed 19 years after the onset of diabetes - Kumiko Tajima; Yushi Hirota; Tomofumi Takayoshi; Wataru Ogawa (Journal of Diabetes Investigation, 2025)
ABSTRACT A 33‐year‐old man presented with short stature, thin build, hearing impairment, Rieger anomaly, and a history of inguinal hernia. He also exhibited characteristic facies, including a triangular face with a small chin, deeply set eyes, and low‐set ears. He was born with intrauterine growth restriction and developed diabetes during adolescence, requiring high‐dose insulin therapy. For 19 years, an accurate diagnosis was not made. We performed direct sequencing of the insulin receptor gene and exons 11–16 of the PIK3R1 gene, identifying a c.1957A>T mutation (p.Lys653*) in the PIK3R1 gene, which confirmed a diagnosis of SHORT syndrome. Suspecting SHORT syndrome in individuals who exhibit some of its typical symptoms may facilitate an accurate diagnosis and enable effective management of this condition.